2021
DOI: 10.1177/08862605211001484
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Father-Perpetration of Maltreatment on Adolescent Health Risk

Abstract: Maltreatment perpetrated by fathers may entail distinct characteristics and threats, and therefore differing effects from maltreatment perpetrated by mothers alone. This study examines the extent to which father perpetration of maltreatment is associated with variability in subsequent adolescent health outcomes relative to mother-alone maltreatment. A sample of youth ( N = 377) with recently completed Child Protective Services investigations concerning reports of maltreatment attributed to fathers and/or mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Not only are mothers’ and fathers’ data used jointly, but also the entire family serves as the unit of analysis in family systems-informed studies such as ours. Given the generally atheoretical nature of prior studies on the topic of mother–father co-involvement in child maltreatment [ 2 , 9 , 10 ], the application of family systems theory is a key contribution of this study, challenging current theoretical models on child abuse to consider the joint roles of mothers and fathers and risk factors that occur at the parental dyad or family level. Our study also importantly informs and contributes to maltreatment prevention policy and practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only are mothers’ and fathers’ data used jointly, but also the entire family serves as the unit of analysis in family systems-informed studies such as ours. Given the generally atheoretical nature of prior studies on the topic of mother–father co-involvement in child maltreatment [ 2 , 9 , 10 ], the application of family systems theory is a key contribution of this study, challenging current theoretical models on child abuse to consider the joint roles of mothers and fathers and risk factors that occur at the parental dyad or family level. Our study also importantly informs and contributes to maltreatment prevention policy and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Another study using NSCAW-II data showed that child maltreatment cases were most likely to be substantiated when both mothers and fathers were involved (approximately 30% in which two parents were involved vs. 20% where either parent was involved alone) [ 9 ]. More recently, a study showed that physical abuse and sexual abuse were 1.5 times more likely to occur in families where fathers were co-involved with the mothers in committing child maltreatment compared to families where only mothers were involved [ 10 ]. That said, given data limitations, the researchers needed to combine families where fathers were solely involved in child maltreatment with families where fathers and mothers were co-involved in child maltreatment, making it difficult to distinguish which group drove the high rates of physical and sexual abuse.…”
Section: Mother–father Co-involvement In Child Maltreatmentmentioning
confidence: 99%
See 1 more Smart Citation